(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The development of Power Take-Off (PTO) systems is crucial for the progress of wave energy technologies. Among the different PTO concepts, direct-drive systems based on linear electrical generators stand out due to their simplicity, robustness, and efficiency, as they minimize energy transformations. Despite their advantages, linear electrical generators face significant challenges, particularly in terms of force density and reactive power capability. These limitations are most evident at low operational speeds, where high currents are required to generate adequate forces, leading to significant Joule losses. Furthermore, the management of reactive power for implementing advanced control strategies, such as reactive or pseudo-optimal wave energy extraction, is hindered by constant energy dissipation. This is particularly problematic at null or low velocities, where Joule losses persist regardless of speed, limiting the use of reactive power Superconducting technology has emerged as a promising solution to these challenges by significantly improving force density while reducing Joule losses. However, the cryogenic systems required for maintaining superconducting conditions impose strict constraints, as all conductor losses, including AC losses associated with oscillating currents, must be minimized. In this context, the paper describes a novel concept for a linear generator based on switched reluctance and superconducting coils, protected under a patented design. To address the issue of AC losses in superconducting cables, we introduce an innovative control strategy for the electronic converter associated with the generator. This strategy is designed to minimize current ripple in the generator phases, reducing oscillation frequencies and, consequently, AC losses. The proposed approach employs a single-pulse switching strategy, where each phase of the converter is activated and deactivated without intermediate semiconductor switching. This eliminates additional ripple in the phase currents. To regulate the force amplitude, the voltage of the DC link connected to the converter is controlled, enabling precise force modulation. The paper provides a comprehensive description of the switching strategy and evaluates its performance under oscillatory motion conditions typical of wave energy converters (WECs). A detailed comparison with conventional strategies demonstrates the proposed approach’s potential to enhance generator efficiency, reduce losses, and improve overall performance. This work highlights the feasibility of integrating superconducting direct-drive PTO systems into WECs, paving the way for more efficient and reliable wave energy technologies.